Asymmetric Synthesis of α, α‐Disubstituted Allylic Amines through Palladium‐Catalyzed Allylic Substitution. Issue 39 (23rd August 2017) - Guo, Wusheng; Cai, Aijie; Xie, Jianing; Kleij, Arjan W.
Abstract: The first asymmetric synthesis of important α, α‐disubstituted N‐alkyl allyl amine scaffolds through allylic substitution is reported. This approach is based on palladium catalysis and features ample scope with respect to both the allylic precursor and amine reagent, and high asymmetric induction with enantiomeric ratios (e.r.) up to 98.5:1.5. The use of less‐reactive anilines is also feasible, providing enantioenriched α, α‐disubstituted N‐aryl allylic amines. Abstract : Take a walk on the wide side : The first asymmetric synthesis of invaluable α, α‐disubstituted N‐alkyl allylic amines was developed using an allylic substitution approach. The catalytic method relies on Pd catalysis, is user‐friendly, and can be accomplished under mild and additive‐free conditions. The wide product scope for these challenging allylic amine scaffolds is the most impressive reported to date, with e.r. values of up to 98.5:1.5.